«HALYC’KE EVANHELIE» AS HISTORICAL, LITERATURE AND LINGUISTIC TREASURE FROM 1144 - Idzio, V.S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
In the article the author studies Ukrainian historical, religious. cultural and linguistictreasure from the year 1144 «Halyc’ke Evanhelie» (Evangelie from Halych Region). Main part of this work is concentrated on the study of the language of Halyc’ke Evanhelie as well as on the historical events which took place from the time of writing ofHalyc’ke Evanhelie till the time of finding it in Moscow.